Rooted in therapeutics: comprehensive analyses of Cannabis sativa root extracts reveals potent antioxidant, anti-inflammatory, and bactericidal properties - Gagné, Valérie; Merindol, Natacha; Boucher, Raphaël; Boucher, Nathalie; Desgagné-Penix, Isabel (Frontiers in Pharmacology, 2024)
Following the legalization of recreational Cannabis in Canada in 2018, the associated waste, including Cannabis roots, has significantly increased. Cannabis roots, comprising 30%–50% of the total plant, are often discarded despite their historical use in Ayurvedic medicine for treating inflammatory and infectious disorders. This study evaluates the phytochemical and therapeutic properties of Cannabis root extracts from a high tetrahydrocannabinolic acid, low cannabidiolic acid cultivar (variety Alien Gorilla Glue). We performed ultra high-performance liquid chromatography coupled with mass spectrometry (UPLC-QTOF-MS) to identify the chemical components of the Cannabis roots. Extracts using water, ethanol and acid-base solvents were tested for antioxidant activity through free radical scavenging, metal chelation, and lipoperoxidation inhibition assays. Mitochondrial membrane protection was assessed using flow cytometry with the MitoPerOx probe in THP-1 monocytic leukemia cells. Anti-inflammatory potential was evaluated by measuring interleukin-6 levels in lipopolysaccharide-stimulated THP-1 cells. Bactericidal/fungicidal efficacy against Escherichia coli, Staphylococcus aureus, and Candida albicans was determined using the p-iodonitrophenyltetrazolium assay. Additionally, we investigated the anticholinesterase activity of Cannabis root extracts, given the potential role of plant alkaloids in inhibiting cholinesterase, an enzyme targeted in Alzheimer’s disease treatments. UPLC-QTOF-MS analysis suggested the presence of several phenolic compounds, cannabinoids, terpenoids, amino acids, and nitrogen-containing compounds. Our results indicated significant antioxidant, bactericidal, and anticholinesterase properties of Cannabis root extracts from both soil and hydroponic cultivation. Extracts showed strong antioxidant activity across multiple assays, protected mitochondrial membrane in THP-1 cells, and exhibited anti-inflammatory and bactericidal/fungicidal efficacy. Notably, soil-cultivated roots displayed superior anti-inflammatory effects. These findings demonstrate the remarkable antioxidant, anti-inflammatory, and anti-microbial activities of Cannabis roots, supporting their traditional uses and challenging their perception as mere waste. This study highlights the therapeutic potential of Cannabis roots extracts and suggests avenues for further research and application.